Organizational Approach to Prevention of Stress at Work and Preservation of Employees’ Mental Health - Glomazić, Hajdana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
Stress at work can be a strong factor endangering the mental health of employees, resulting in lower work motivation, job dissatisfaction, reduced productivity, and associated absenteeism or presenteeism. In turn, common effects are financial losses of both the organization and society as a whole. Managers are tasked with devising a functional organizational approach to prevent stress at work, in order to reduce damage to a minimum. The subject of this paper is to determine the relationship between the consequences of stress in the workplace and organizational skills needed to recognize them and act preventively on them. The aim of this paper is to examine which strategies for prevention and recognition of stress at work are available to organizations in order to preserve employees’ mental health. The results have shown that organizations do not sufficiently recognize the importance of preventive action in order to reduce stress at work, either personally, in terms of employees’ mental health care and wellbeing, or in organizational and societal terms, in terms of financial losses on that basis. This is especially true for small and medium enterprises.